Trained Panel Evaluation of Upper 2/3 Prime Beef Strip Loin Steaks - Katelynn E. Wallace (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: The objective of this study was to evaluate trained sensory panel perceptions of beef strip loin steaks representing four marbling categories: Super Prime (moderately abundant and abundant), Low Prime, Top Choice (modest and moderate), and Low Choice (small). Study Description: Beef strip loins (n = 15/grade) representing four marbling categories were collected from a commercial packing facility, fabricated into approximately 1-in. steaks, and aged 28 days before analysis. Steaks were cooked to one of three degrees of doneness ([DOD]; Rare = 140°F, Medium = 160°F, and Well-done = 170°F) and used for trained panels, Warner-Bratzler shear force (WBSF), slice shear force, pressed juice percentage, and cook loss. Trained panelists (n = 8) rated samples on initial and sustained juiciness, myofibrillar tenderness, connective tissue amount, overall tenderness, and beef flavor intensity. The Bottom Line: Super Prime steaks consistently rated higher than the other grades in trained sensory evaluations, indicating that marketing them as a premium tier could boost value and ensure a more consistent, high-quality eating experience.
Keywords: beef; USDA Prime; palatability